Biomass production and carbon sequestration potential of rubber (Hevea brasiliensis Muell. Arg.) plantation in Hilly zone of Karnataka - Noori, Shahbaz; Inamati, S.S. (Indian Journal of Agroforestry, 2020)
Sequestering atmospheric CO2 through tree cultivation is an environmentally acceptable option. Quantitative information about biomass growth and carbon sequestration by crops is a fundamental knowledge that can be used to improve the crop yield per unit of cultivation area. The present study was conducted to determine the biomass production and carbon sequestration potential of Hevea brasiliensis clone RRII 105 in different aged rubber plantations raised in low and high rainfall zones of Karnataka. The biomass production and carbon sequestration were observed to be double in plantation of different age groups situated in high rainfall zone (Sagara) than low rainfall zone (Mundgod).